2020
DOI: 10.1016/j.landurbplan.2019.103672
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the consequences of roads for wildlife population dynamics

Abstract: Rapidly expanding road networks have been a key driver of the fragmentation and isolation of many wildlife species, and are a source of significant mortality due to collisions with vehicles. But not all animals are affected equally by transportation infrastructure, and in most cases little is known about the population-scale consequences of roads for wildlife. Even less information is available to characterize species' behavioral responses to roads. Although research shows that maned wolves (Chrysocyon brachyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 40 publications
0
17
0
3
Order By: Relevance
“…Rapidly expanding human populations are now affecting wildlife species globally ( Bongaarts, 2019 ). Growing anthropogenic activities cause loss and fragmentation of natural habitat, leading to increased road mortality, reduced wildlife movements and population decline ( Carvalho et al , 2009 ; Abra et al , 2018 ; de Souza et al , 2018 ; Barbosa et al , 2020 ). These direct threats often amplify conflict between wildlife and people and increase exposure of wildlife to domestic animals and zoonotic diseases ( Paula and DeMatteo, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapidly expanding human populations are now affecting wildlife species globally ( Bongaarts, 2019 ). Growing anthropogenic activities cause loss and fragmentation of natural habitat, leading to increased road mortality, reduced wildlife movements and population decline ( Carvalho et al , 2009 ; Abra et al , 2018 ; de Souza et al , 2018 ; Barbosa et al , 2020 ). These direct threats often amplify conflict between wildlife and people and increase exposure of wildlife to domestic animals and zoonotic diseases ( Paula and DeMatteo, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, research has shown that faecal glucocorticoid metabolites concentrations increase with increasing distance from natural habitat patches and during the peak of harvest activity in croplands ( Spercoski et al , 2012 ; Vynne et al , 2014 ). Other anthropogenic effects include higher exposure to pathogens from domestic animals ( Curi et al , 2012 ) and increased risks of roadkill ( Barbosa et al , 2020 ). In addition, the global ex situ population, which is kept as a safeguard against extinction of wild population, suffers from low reproductive success and sub-optimal health ( Songsasen and Rodden, 2010 ; Jones et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic simulations created by such models link the behavior and fates of individuals to their locations, supporting evaluation of the effects of environmental change on movement, population sizes, distributions, and genetic diversity (e.g., Heinrichs et al 2019aHeinrichs et al , 2019bNogeire-McRae et al 2019). Accordingly, the results of these models can project the population-level effects of barriers to movement and alternative reserve designs and be applied to examine the effects of compensatory mitigation (Barbosa et al 2019). If there is a desire to project future occupancy given potential changes in land use or land cover, such changes can be simulated by modifying the input environmental data layers.…”
Section: Ecology Well Known Distribution Restrictedmentioning
confidence: 83%
“…As part of the transportation infrastructure, roads have well-known detrimental effects on wildlife, including mammals [ 1 , 2 , 3 ]. Their impacts are well-documented worldwide [ 4 , 5 , 6 ]. In an increasing number of landscapes, movements of animals, particularly wide-ranging large mammals, come into contact with and require the crossing of roads.…”
Section: Introductionmentioning
confidence: 99%